2020
DOI: 10.1002/qua.26566
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles investigations on the ground‐state bulk properties and lattice constant dependent half‐metallic ferrimagnetism of Mn2NbSi full‐Heusler compound

Abstract: The ground‐state bulk properties and lattice constant dependent half‐metallic ferrimagnetism of L21 Mn2NbSi were systematically investigated using first‐principles calculations within the framework of density functional theory. The calculated ground‐state bulk properties are found to be in good agreement with the available values. The calculated elastic constants and related properties showed that the compound is mechanically stable, intrinsically ductile and elastically anisotropic. The calculations of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, there are some HM alloys have no HM properties in the equilibrium lattice constant [33][34][35][36]. It is necessary to change the lattice constant under specific pressure conditions in order to achieve HM, which significantly restricts its practical application for stability consideration, let alone the HM lattice interval is not so wide.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some HM alloys have no HM properties in the equilibrium lattice constant [33][34][35][36]. It is necessary to change the lattice constant under specific pressure conditions in order to achieve HM, which significantly restricts its practical application for stability consideration, let alone the HM lattice interval is not so wide.…”
Section: Introductionmentioning
confidence: 99%
“…In another substitution study, Ram, et al 18 investigated Mn 2 ZnSi (1−x) Ge x alloys and found that the presence of half-metallic ferromagnetism and bandgap was due to antiparallel alignment of Mn atom at all studied concentrations. Very recently, Liu, et al 19 studied another imperative Mn based alloy, Mn 2 NbSi, which has a potential application in spintronic devices due to its half-metallic ferrimagnetism with low magnetic moment. While, Buchelnikov, V.D, et al 20 recently investigated the response of ferromagnetism under pressure.…”
mentioning
confidence: 99%